The syntax and semantics of pseudo-incorporation - Borik, Olga, 1972-; Gehrke, Berit (Syntax and semantics ;, 2015)
This volume brings together recent research on the semantics and syntax of pseudo-incorporation (PI), which is a construction of crucial significance for linguistic explorations as it brings together several fundamental areas of linguistic research, such as morphology, argument structure, modification, discourse and information structure. The main purpose of the book is to further improve our understanding of the phenomenon, expand the domain of inquiry by bringing into focus new empirical data from a wide array of languages, offer new formal analyses of PI, and strengthen the links with other related phenomena, such as bare nominals. Focusing on various properties of PI the articles in this volume set an excellent ground for further expansion of research in PI and related topics.